2011
DOI: 10.1111/j.1365-3040.2011.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration from shoots triggers diurnal changes in root aquaporin expression

Abstract: Root hydraulic conductivity (Lpr) and aquaporin amounts change diurnally. Previously, these changes were considered to be spontaneously driven by a circadian rhythm. Here, we evaluated the new hypothesis that diurnal changes could be triggered and enhanced by transpirational demand from shoots. When rice plants were grown under a 12 h light/12 h dark regime, Lpr was low in the dark and high in the light period. Root aquaporin mRNA levels also changed diurnally, but the amplitudes differed among aquaporin isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
146
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 44 publications
12
146
2
1
Order By: Relevance
“…These data suggest that OsPIP2;5 not only governs the longer term (hours to days) response of root Lp in rice to changes in transpirational water flow but is also involved in the shorter term response (minutes to hours). Figure 5 summarizes the findings of Ahamed et al (2012), Sakurai-Ishikawa et al (2011) and the present study on rice, and also includes the only comparable study on another plant species, soybean (Glycine max. L) by Vandeleur et al (2014).…”
Section: Rice Root Pip Aqp Expression In Response To Shoot Removalmentioning
confidence: 99%
See 4 more Smart Citations
“…These data suggest that OsPIP2;5 not only governs the longer term (hours to days) response of root Lp in rice to changes in transpirational water flow but is also involved in the shorter term response (minutes to hours). Figure 5 summarizes the findings of Ahamed et al (2012), Sakurai-Ishikawa et al (2011) and the present study on rice, and also includes the only comparable study on another plant species, soybean (Glycine max. L) by Vandeleur et al (2014).…”
Section: Rice Root Pip Aqp Expression In Response To Shoot Removalmentioning
confidence: 99%
“…Previous studies (Sakurai et al, 2005(Sakurai et al, , 2008Guo et al, 2006;Sakurai-Ishikawa et al, 2011) and our own preliminary experiments (not shown) on the Bala rice cultivar analysed showed that all three PIP1 genes and all PIP2 genes except OsPIP2;7 and OsPIP2;8 are expressed in roots at significant, or at least reproducibly detectable levels. Therefore, the latter two rice PIP genes were not included in the present analyses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations